PENGARUH E-COMMERCE DAN E-BUSSINES DALAM PENGAMBILAN KEPUTUSAN UNTUK BERWIRAUSAHA PADA KALANGAN MAHASISWA FEB UNISMA - Nuris Shobach; Moh. Amin; Afifudin Afifudin (e_Jurnal Ilmiah Riset Akuntansi, 2021)
This study discusses the influence of e-commerce and e-business in decision making for entrepreneurship. The type of data in this study is quantitative. The sampling method used the slovin formula with the data collection method using a questionnaire via google form. The population in this study were students of the Accounting Department, Faculty of Economics and Business, Islamic University of Malang, namely active students from the 2017 – 2019 class of 780 students who had taken entrepreneurship and AIS courses. The results of this study indicate that e-commerce has an effect on entrepreneurial decision making and e-business has an effect on entrepreneurial decision making. While the two variables simultaneously show a significant influence on decision making for entrepreneurship.Keywords: E-commerce, E-bussines, Entrepreneurship, decision making.